2016
DOI: 10.1007/s11046-016-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assays for Specific Detection of Fungi of Scopulariopsis and Microascus Genera and Scopulariopsis brevicaulis Species

Abstract: PurposeFungi of Scopulariopsis and Microascus genera cause a wide range of infections, with S. brevicaulis being the most prevalent aetiological agent of mould onychomycosis. Proper identification of these pathogens requires sporulating culture, which considerably delays the diagnosis. So far, sequencing of rDNA regions of clinical isolates has produced ambiguous results due to the lack of reference sequences in publicly available databases. Thus, there is a clear need for the development of new molecular meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Additionally, it has been reported that for Wood’s lamp examination, only 50% of M. canis infections can be detected, while most other dermatophytes (such as T. mentagrophytes ) do not produce fluorescence [ 34 ]. Another common diagnostic method in clinical practice is a direct microscopic examination, which could be a simple and rapid way to screen for microconidia and hyphae, however, only >85% of cases can be accurately diagnosed [ 3 ]. Importantly, the professional requirements for the microscopic examination have high professional requirements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been reported that for Wood’s lamp examination, only 50% of M. canis infections can be detected, while most other dermatophytes (such as T. mentagrophytes ) do not produce fluorescence [ 34 ]. Another common diagnostic method in clinical practice is a direct microscopic examination, which could be a simple and rapid way to screen for microconidia and hyphae, however, only >85% of cases can be accurately diagnosed [ 3 ]. Importantly, the professional requirements for the microscopic examination have high professional requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the professional requirements for the microscopic examination have high professional requirements. In addition, time-consuming and demanding (about 1–2 weeks) are two recognized disadvantages of fungal culture, which can delay the diagnostic outcome and treatment [ 3 ]. Molecular tools are increasingly used in the laboratory for fungal identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, S. brevicaulis is a keratinolytic and chitin-degrading mold widely distributed in the soil, plant materials, skin, and feathers [ 38 ]. It is considered a common contaminant species, but it can cause infections in humans, in which it may be responsible for endocarditis [ 39 ], onychomycosis [ 40 ], and keratitis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…belongs to the ascomycete family Microascaceae and is a ubiquitous, saprobic mold found worldwide in soil, plant debris, wood, paper, animal matter, air, and moist indoor environments (Abbott et al 1998;Anandan et al 2008). The genus Scopulariopsis, and predominantly S.brevicaulis, is known to be an opportunistic pathogen that is thought to cause invasive (immunocompetent and immunosuppressed patients) and noninvasive infections such as, onychomycosis, keratitis, conjunctivitis, endocarditis, and disseminated in animals and humans (Ragge et al 1990;Tosti et al 1996;Iwen et al 2012;Cawcutt et al 2015;Kordalewska et al 2016;Hampson et al 2019).…”
Section: Introductionmentioning
confidence: 99%